A simplified model for evaluating eVTOL conceptual designs and with example results for three types of eVTOL aircraft configurations - Yip, S.L.K.; Hoong, A.K.J.; Wang, J. (My University, 2022)
eVTOL Performance Analysis Tool, known as ePERF is a MATLAB-based analysis developed at NTU specifically for evaluating the performance of different types of eVTOL aircraft and is ideal for eVTOL aircraft conceptual and preliminary design phases. The framework is built to have a modular nature allowing for rapid trade studies of different sizing parameters, and it provides a representative performance evaluation of the eVTOL in all phases of flight. ePERF consists of three main modules: a rotary wing module, a drag estimation module for forward flight and an energy module for range calculation. Momentum theory is used for hover calculations. A component level drag build-up method is used for cruise calculations. The energy model considers the input battery parameters and results from the other two modules to compute the energy requirements of the eVTOL based on a given mission profile. The outputs of ePERF include the power and energy requirements for each flight phase, an estimated attainable range, as well as the velocity for best range. In this paper, the ePERF is explained and then it is used to estimate the performance for three different example eVTOL aircraft: (A) a Lift + Cruise type like Beta Technologies - Alia, (B) a tiltrotor type like Joby Aviation - S4, and (C) a fixed Lift + Tiltrotor type like Vertical Aerospace - VX4. The results show that reducing the structural weight of the eVTOL aircraft is one of the key factors in achieving best performance.